Nilai Pendidikan Karakter Dalam Kitab Washaya Al-Aba’ Li Al-Abna Karya Muhammad Syakir Al-Iskandari - Muhammad Basarrudin (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
This research aims to identify the character education values ​​contained in the book Washaya al-Aba' li al-Abna Muhammad Syakir and the role of his opinion on the richness of character education values. It is hoped that this research can be used as a source or reference in efforts to develop education and character as a whole, especially character education according to Islam. It can also be used as a reference to facilitate understanding of character education and as a reference for relevant research in the future. This research method is qualitative and uses a narrative biography method. By using a descriptive presentation approach, this autobiography of the character's thoughts combines the ideas of character education from his work. Library research, or library research, is a research method that involves books, articles, notes and electronic media. with primary sources from the book Washaya al Aba Li al-Abna and secondary sources from study books. In this research, data collection was carried out through the documentation method, which includes searching for data through variables such as notes, books, and articles, among others. The author used a content analysis study to analyze the data; they analyzed the data textually based on the contents of the book. The research results show that the book Washaya al Aba Li al-Abna contains 17 educational character values, divided into two categories: 10 character values ​​fall into the moral category and 7 character values ​​fall into the performance category. Faith and piety, love and obedience to the Messenger of Allah, respect for parents, respect for teachers, truth or honesty, nobility or self-respect, patience, sincerity and a simple life are moral characters. Performance characteristics also include trust, discipline, hard work, never giving up, love of the country, interest in reading or literacy knowledge, and concern for the environment.